Effect of Substituting LiBF4 for LiPF6 in High Voltage Lithium-Ion Cells Containing Electrolyte Additives. Issue 8 (8th June 2016) - Ellis, L. D.; Xia, J.; Louli, A. J.; Dahn, J. R.
Abstract : This work evaluates the performance of LiBF4 -containing electrolytes in lithium-ion cells charged to high voltages (>4.4 V) and explores the compatibility of LiBF4 with additives known to improve the performance of LiPF6 -based electrolytes. It was found that the benefit imparted by LiBF4 is lost when cells are charged beyond 4.4 V, at which point electrolyte oxidation causes gas evolution and impedance growth. In the case of LiBF4, impedance growth is shown to be due to increased charge transfer resistance at the negative electrode, indicating poor passivation of the negative electrode. Of the additives tested, only those containing prop-1-ene-1, 3-sultone benefit cells with LiBF4 electrolyte at high voltage.